Effect of rebleeding on the course and incidence of vasospasm after subarachnoid hemorrhage - Lord, A.S. (Lippincott Williams & Wilkins, 2012)
OBJECTIVE: Rebleeding of an aneurysm is a leading cause of morbidity and mortality after subarachnoid hemorrhage (SAH). Whereas numerous studies have demonstrated the risk factors associated with rebleeding, few data on complications of rebleeding, including its effect on the development of delayed cerebral ischemia (DCI), are available. METHODS: A nested case-control study was performed on patients with rebleeding and control subjects matched for modified Fisher scale, Hunt-Hess grade, age, and sex previously entered into a prospective database. Rebleeding was defined as new hemorrhage apparent on repeat CT with or without new symptoms. Incidence and time course of DCI and hospital complications were compared. A secondary analysis of DCI and hospital complications was also performed on subjects surviving to postbleed day 7. RESULTS: We identified 120 patients with rebleeding and 359 control subjects from 1996 to 2011. The rebleeding rate was 8.6%. In both the primary and secondary analyses, there was no difference in the incidence of DCI or its time course (29% vs 27%, p = 0.6; 7 ± 5 vs 7 ± 6 days, p = 0.9 for primary analysis; 39% vs 31%, p = 0.1, 7 ± 5 vs 7 ± 6 days, p = 0.6 for the secondary analysis). In a multivariate logistic regression model, rebleeding was associated with the complications of hyponatremia, respiratory failure, and hydrocephalus. Patients with rebleeding had higher rates of mortality, brain death, and poor outcomes. CONCLUSIONS: Rebleeding after SAH is associated with multiple medical and neurologic complications, resulting in higher morbidity and mortality, but is not associated with change of incidence or timing of DCI.